Defining Behavior Patterns Towards Exclusive Breastfeeding Using Latent Class Analysis - Pryscila de Argolo Cerqueira; Leila D A F Amorim; Tatiana de O Vieira; Janaina S Dias; Heli V Brandao; Graciete O Vieira (Mazandaran University of Medical Sciences, 2018)
Background: The interruption of exclusive breastfeeding (EBF) is worrying. This study aimed to identify behavior patterns towards EBF among mothers and health professionals. Methods: This is a cross-sectional analysis of a cohort consisting of 1309 women. We used latent class analysis (LCA), considering 15 indicators for defining 4 constructs: maternal emotional state, availability to breastfeed, maternal attitude, and health professional's attitude towards breastfeeding. Results: Among mothers, 36.5% were classified as being in an unfavorable emotional state; they presented a higher probability of feeling tired, nervous, and sad; 14.7% had less availability to breastfeed and a higher probability of including primiparous and partners not helping to care for the child; 41.5% had negative attitude towards breastfeeding, including mothers more likely to give a pacifier and bottle. Among health professionals, 62.0% were categorized with unfavorable attitude towards breastfeeding, not providing guidance on breastfeeding in the hospital.